Creative Photography - Malkin, Russ (BCA, 1991)
Activities and projects for young photographers including montage, a panorama and a storyboard. Gives advice on how to avoid making common mistakes, tips on different types of photography, and information on cameras and film.
Keywords: Juvenile literature-Arts and crafts-Photography-Non-Fiction